Meconium Aspiration Treated with Extra-Corporeal Membrane Oxygenation - Iqbal Mustafa; Syarif Rohimi; Soemanto Soemanto; Embing Sjamsudin; Hartoyo Hartoyo; Heru Samudro; Jusuf Rachmat; Budining Wirastari; Edi M. Halimun; Zuswahyudha Zuswahyudha; Anna Ulfah Rahayoe (Indonesian Pediatric Society, 1998)
We report the first Indonesian baby delivered by cesarean section and developed into metabolic acidosis, severe respiratory failure due to meconium aspiration accompanied by right pneumothorax. The case was successfully managed with extracorporeal membrane oxygenation (ECMO).